The Potential of Serum Exosomal hsa_circ_0028861 as the Novel Diagnostic Biomarker of HBV-Derived Hepatocellular Cancer - Wang, Yuanxiao; Pei, Lin; Yue, Zhihong; Jia, Mei; Wang, Hui; Cao, Lin-Lin (Frontiers in Genetics, 2021)
Hepatitis B virus (HBV)-derived hepatocellular cancer (HCC) is a serious threat to human health, especially in China. There is no highly sensitive and specific HCC biomarker at present, which makes it difficult to detect HCC at the early stage. Serum exosomal circular RNAs (circRNAs) have been reported as novel diagnostic and prognostic biomarkers of cancers. In the present study, we aimed to explore the diagnostic performance of serum exosomal circRNAs for HBV-derived HCC screening. At first, many circRNAs were found differentially expressed in the serum exosomes of HCC individuals by microarray analysis. The validation of dysregulated circRNAs by qRT-PCR revealed that serum exosomal hsa_circ_0028861 was decreased in HCC compared to chronic HBV and cirrhosis. Then hsa_circ_0028861 was identified as a novel biomarker for HCC diagnosis, with an area under the ROC curve (AUC) of 0.79 for discriminating HCC from chronic HBV and cirrhosis individuals. Hsa_circ_0028861 was capable of detecting small (AUC = 0.81), early-stage (AUC = 0.82) and AFP-negative [AFP (-)] (AUC = 0.78) tumors as well. The combination of hsa_circ_0028861 and AFP exhibited better diagnostic ability (AUC = 0.86 for discriminating HCC from chronic HBV and cirrhosis). Moreover, bioinformatics prediction suggested that hsa_circ_0028861 might influence HCC progression by regulating its targeted microRNAs (miRNAs) and downstream tumor-related signaling pathways. Collectively, our study reveals a novel diagnostic tool for HBV-derived HCC.